Hamka's Thoughts on Taqwa Democracy - Herdiawanto, Heri; Subekti, Valina Singka; Noor, Firman (Jurnal Penelitian Politik, 2023)
The phenomenon of Western democracy as an ideal political system, has been continuously debatable among Muslims. Muslim societies respond to Western democracy with three groups of attitudes, namely acceptance (“pro”), rejection (contra, “con”) and critical accommodation. The main argument of the contra camp is the rejection of secularism as the main characteristic of Western democracy. On the other hand, the pro and critical accommodative camps consider democracy to achieve Islamic goals. One of the prominent Indonesian thinkers in the critical accommodative camp was Hamka or Haji Abdul Malik Karim Amrullah. Hamka (1908–1981), one of the leading Islamic intellectuals in Indonesia in the modern era, was known for his monumental work, Tafsir Al Azhar. Hamka was well-known as an Indonesian ulama (cleric), Muhammadiyah activist, and Masyumi Party politician who was directly involved in the ideological debates in the Constituent Assembly in Bandung (1956–1959). This paper presents a descriptive-analytical research report conducted in 2015–2019. This aims to explain Hamka’s view of democracy through Islamic perspective. Hamka believes that democracy is the way to achieve Islamic goals. Tauhid and shura are the basis of Hamka’s thoughts about democracy. In contrast to secular Western democracy, Hamka coined the Islamic concept of democracy, which was named “Taqwa Democracy”.